A modified aluminosilicate inorganic mesoporous material and preparation method thereof
Through nitrate roasting and chitosan modification methods, the specific surface area and adsorption performance of aluminosilicate are improved, and the problems of insufficient adsorption performance and process complexity of natural aluminosilicate in wastewater treatment are solved, achieving high efficiency , economical nitrogen removal and phosphorus removal effects.
Patent Information
- Application Number
- CN202411207838.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Natural aluminosilicates have problems in sewage treatment with high impurity content, narrow pores, small specific surface area and complex modification methods, resulting in limited adsorption performance and it is difficult to achieve the goal of efficient adsorption and simplification of processes at the same time.
By calculating aluminosilicate in nitrate solution and modifying chitosan, adjusting its particle size and specific surface area, an inorganic mesoporous material with a specific surface area of 30m²/g to 40m²/g is prepared to enhance its ammonia nitrogen and Phosphorus adsorption capacity and simplify the process.
It significantly improves the adsorption efficiency of aluminosilicate to ammonia nitrogen and phosphorus, has good stability, is suitable for the removal of various pollutants, reduces production costs, and broadens the scope of application.
Smart Images

Figure CN118719011B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, and in particular to an inorganic mesoporous material of modified aluminosilicate and a preparation method thereof. Background Art
[0002] The development of efficient and economical nitrogen and phosphorus removal technologies is of great significance for protecting water resources and maintaining ecological balance. Among the many nitrogen and phosphorus removal methods, adsorption has attracted widespread attention due to its simple operation and low cost. Aluminosilicate, as a cheap and readily available natural mineral, has good adsorption properties due to its porous structure and is widely used in the treatment of ammonia nitrogen and phosphorus polluted water bodies.
[0003] However, natural aluminosilicates still have many limitations in practical applications: 1) High impurity content: Natural aluminosilicates often contain high impurity components, which not only reduce their adsorption efficiency, but may also cause secondary pollution to water bodies. 2) Narrow pores: The pore size of natural aluminosilicates is relatively narrow, which limits their adsorption capacity for macromolecular pollutants, especially for ammonia nitrogen and phosphorus ions with good solubility. The adsorption effect is limited. 3) Small specific surface area: A small specific surface area means limited adsorption sites, which is difficult to meet the needs of large-scale water treatment. 4) Complex modification methods: At present, most of the modification methods for aluminosilicates have the problems of single treatment function or complex procedures, and it is difficult to achieve the goals of efficient adsorption and simplified process at the same time.
[0004] Mesoporous materials have shown broad application prospects in many fields due to their high specific surface area, large pore volume, and unique and adjustable mesoporous structure. Especially in the field of nanomedicine, mesoporous materials can load guest molecules into the pores and achieve responsive release and delivery through pore switches. This feature provides new ideas for drug delivery, gene therapy, etc. However, in the field of water treatment, the application of mesoporous materials still faces some challenges, such as how to effectively combine the advantages of mesoporous structure with the cheap availability of aluminosilicates to develop economical and efficient nitrogen and phosphorus removal materials.
[0005] In view of the above background, a new type of aluminosilicate modification scheme is urgently needed to solve the following problems: 1) Improve adsorption performance: enhance the adsorption capacity of aluminosilicate for ammonia nitrogen and phosphorus through modification, especially the adsorption efficiency in low-concentration polluted water. 2) Simplify the modification process: seek a simple and easy-to-operate modification method to reduce production costs and facilitate large-scale promotion and application. 3) Maintain material stability: ensure that the modified aluminosilicate can still maintain stable adsorption performance in complex water environments to avoid secondary pollution. 4) Broaden the scope of application: make the modified aluminosilicate not only suitable for the removal of a single pollutant, but also can treat multiple pollutants at the same time, improving the comprehensive effect of water treatment. Summary of the invention
[0006] In order to solve the above technical problems, the present application provides an inorganic mesoporous material of modified aluminosilicate and a preparation method thereof.
[0007] To achieve the above objectives, this application is implemented through the following technical solutions:
[0008] The present application provides a method for preparing an inorganic mesoporous material of modified aluminosilicate, comprising the following steps:
[0009] S1. After crushing the aluminosilicate, screen out aluminosilicate particles of 80-100 meshes;
[0010] S2, soaking the aluminosilicate particles obtained in step S1 in a nitrate solution with a concentration of 1 mol / L to 6 mol / L for 12 h to 24 h, wherein the volume of the nitrate solution corresponding to each 1 g of the aluminosilicate particles is 10 mL to 60 mL, filtering, drying at 95° C. to 110° C., and then calcining at 400° C. to 500° C. for 1 h to 2 h to obtain primary modified aluminosilicate particles;
[0011] S3. Soak the primary modified aluminosilicate particles obtained in step S2 in a chitosan solution with a mass concentration of 3% to 5% and a temperature of 40°C to 60°C for 0.5h to 3h, then filter and wash with water, and dry at 95°C to 110°C to obtain an inorganic mesoporous material of modified aluminosilicate.
[0012] As a further improvement of the present application, the specific surface area of the aluminosilicate is 14 m² / g to 16 m² / g.
[0013] As a further improvement of the present application, the aluminosilicate is at least one of sodium aluminosilicate, potassium aluminosilicate, and calcium aluminosilicate.
[0014] As a further improvement of the present application, in step S2, the nitrate is any one of sodium nitrate and potassium nitrate.
[0015] As a further improvement of the present application, in step S2, the concentration of the nitrate solution is 4 mol / L, the volume of the nitrate solution per 1 g of the aluminosilicate particles is 40 mL, and the soaking time is 12 h.
[0016] As a further improvement of the present application, in step S2, the calcination temperature is 400°C and the calcination time is 1 hour.
[0017] As a further improvement of the present application, in step S3, the chitosan solution is an alkaline chitosan solution with a pH value of 9.5 to 10.5.
[0018] As a further improvement of the present application, in step S3, the mass concentration of the chitosan solution is 5%, the temperature of the chitosan solution is 50° C., and the immersion time in the chitosan solution is 1 hour.
[0019] To achieve the above objectives, the present application provides an inorganic mesoporous material of modified aluminosilicate prepared according to the above-mentioned preparation method.
[0020] As a further improvement of the present application, the specific surface area of the inorganic mesoporous material of the modified aluminosilicate is 30 m² / g to 40 m² / g.
[0021] The beneficial effect of the present application is that the present application provides a method for preparing an inorganic mesoporous material of modified aluminosilicate, which can stably prepare an inorganic mesoporous material of modified aluminosilicate with a stable specific surface area of 30m² / g to 40m² / g through nitrate calcination modification, alkaline chitosan modification treatment, and by regulating the particle size, specific surface area and concentration of nitrate solution of aluminosilicate, the solid-liquid ratio of aluminosilicate particles to nitrate solution, calcination time, calcination temperature, pH value, mass fraction and temperature of chitosan solution, and the minimum size of the internal pores of the mesoporous material can reach sub-nanometer level.
[0022] In addition, direct roasting without water washing after soaking in nitrate solution can effectively avoid secondary pollution of nitrate washing waste liquid. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the internal pore structure of the inorganic mesoporous material of modified aluminosilicate in Example 1;
[0024] Figure 2 This is a transmission electron microscopy image of the internal pore structure of the inorganic mesoporous material of modified aluminosilicate in Example 1. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0026] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with specific implementation methods.
[0027] Example 1
[0028] After crushing the natural sodium aluminosilicate, the sodium aluminosilicate particles with a mesh size of 80 to 100 are screened out, wherein the specific surface area of the sodium aluminosilicate particles with a mesh size of 80 to 100 is 15.63 m² / g, and the sodium aluminosilicate particles with a mesh size of 80 to 100 are soaked in a sodium nitrate solution with a concentration of 4 mol / L for 24 hours, and the volume of the sodium nitrate solution corresponding to each 1g of the sodium aluminosilicate particles is 40 mL, and then the sodium aluminosilicate particles are taken out for solid-liquid separation by vacuum filtration, and dried at 105°C, and then the dried sodium aluminosilicate particles are placed in a muffle furnace, and the muffle furnace is heated to 400°C at a speed of 10K / min, and the sodium aluminosilicate particles are taken out after being kept at a constant temperature of 400°C for 1 hour, and then cooled to room temperature in a dryer to obtain sodium nitrate roasted modified sodium aluminosilicate;
[0029] The sodium nitrate calcined modified sodium aluminosilicate particles were then immersed in a 5% chitosan solution at a temperature of 50°C for 1 hour, wherein the pH value of the chitosan solution was 9.5-10.5, and vacuum filtration was performed for solid-liquid separation. After washing with water, the particles were dried at 100°C to obtain an inorganic mesoporous material of modified aluminosilicate. The specific surface area of the material was found to be 35 m² / g.
[0030] The inorganic mesoporous material of modified aluminosilicate prepared above was scanned and tested by scanning electron microscopy and transmission electron microscopy. The scanning electron microscopy image of the internal pore structure of the inorganic mesoporous material of modified aluminosilicate obtained is as follows: Figure 1 As shown by Figure 1 It can be seen that there are 3 μm pores inside the inorganic mesoporous material of modified aluminosilicate. The transmission electron microscopy image of the internal pore structure of the inorganic mesoporous material of modified aluminosilicate is as follows: Figure 2 As shown by Figure 2 It can be seen that there are 5 nm pores inside the inorganic mesoporous material of modified aluminosilicate. Figure 1 and Figure 2 It can be seen that the internal pore size of the inorganic mesoporous material of modified aluminosilicate obtained in this example is at the mesoporous level, even reaching the sub-nanometer level.
[0031] Example 2
[0032] The difference between this embodiment and embodiment 1 is that the concentration of the selected sodium nitrate is 1 mol / L.
[0033] Example 3
[0034] The difference between this embodiment and embodiment 1 is that the concentration of the selected sodium nitrate is 2 mol / L.
[0035] Example 4
[0036] The difference between this embodiment and embodiment 1 is that the concentration of the selected sodium nitrate is 6 mol / L.
[0037] Example 5
[0038] The difference between this embodiment and embodiment 1 is that the volume of the nitrate solution corresponding to each 1g of the sodium aluminosilicate particles is 10mL.
[0039] Example 6
[0040] The difference between this embodiment and embodiment 1 is that the volume of the nitrate solution corresponding to each 1g of the sodium aluminosilicate particles is 20mL.
[0041] Example 7
[0042] The difference between this embodiment and embodiment 1 is that the volume of the nitrate solution corresponding to each 1g of the sodium aluminosilicate particles is 60mL.
[0043] Example 8
[0044] The difference between this embodiment and embodiment 1 is that the temperature of the muffle furnace is raised to 500° C. at a rate of 10 K / min, and the mixture is taken out after being kept at a constant temperature of 500° C. for 1 hour.
[0045] Example 9
[0046] The difference between this embodiment and embodiment 1 is that the sodium aluminosilicate particles of 80-100 meshes are immersed in a potassium nitrate solution with a concentration of 4 mol / L for 24 hours, and the volume of the potassium nitrate solution corresponding to each 1 g of the sodium aluminosilicate particles is 40 mL.
[0047] Example 10
[0048] The difference between this embodiment and embodiment 1 is that natural potassium aluminosilicate is used instead of natural sodium aluminosilicate.
[0049] Embodiment 11
[0050] The difference between this embodiment and embodiment 1 is that natural calcium aluminosilicate is used instead of natural sodium aluminosilicate.
[0051] Example 12
[0052] The difference between this embodiment and embodiment 1 is that natural calcium aluminosilicate, natural potassium aluminosilicate and natural sodium aluminosilicate are used instead of natural sodium aluminosilicate.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that the concentration of the selected sodium nitrate is 0.5 mol / L.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 1 is that the concentration of the selected sodium nitrate is 10 mol / L.
[0057] Comparative Example 3
[0058] The difference between this comparative example and Example 1 is that the volume of the nitrate solution corresponding to each 1g of the sodium aluminosilicate particles is 5mL.
[0059] Comparative Example 4
[0060] The difference between this comparative example and Example 1 is that the volume of the nitrate solution corresponding to each 1g of the sodium aluminosilicate particles is 100mL.
[0061] Comparative Example 5
[0062] The difference between this comparative example and Example 1 is that the temperature of the muffle furnace is raised to 300° C. at a rate of 10 K / min, and the muffle furnace is taken out after being kept at a constant temperature of 300° C. for 1 hour.
[0063] Comparative Example 6
[0064] The difference between this comparative example and Example 1 is that the temperature of the muffle furnace is raised to 600° C. at a rate of 10 K / min, and the muffle furnace is taken out after being kept at a constant temperature of 600° C. for 1 hour.
[0065] The effect of using the inorganic mesoporous material of modified aluminosilicate prepared in Example 1 to treat sewage with different initial concentrations is shown in Table 1.
[0066] Table 1: Ammonia nitrogen, total phosphorus concentration and removal rate before and after different initial sewage concentrations
[0067]
[0068] As can be seen from Table 1, the technical solution provided in the present application has an ammonia nitrogen removal rate of more than 90% for sewage containing an ammonia nitrogen concentration of 2 mg / L to 150 mg / L, and a total phosphorus removal rate of more than 90% for sewage containing a total phosphorus concentration of 0.5 mg / L to 2 mg / L.
[0069] The inorganic mesoporous materials of modified aluminosilicate prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were used to carry out denitrification and phosphorus removal treatment steps for sewage of the same concentration. Before treatment, the initial concentration of ammonia nitrogen in the sewage was 10 mg / L, and the initial total phosphorus concentration was 1.5 mg / L. The dosage of the inorganic mesoporous materials of modified aluminosilicate was 35 g / L, and the reaction time was 1 day. The effects are shown in Table 2.
[0070] Table 2: Ammonia nitrogen, total phosphorus concentration and removal rate before and after different sodium nitrate concentrations
[0071]
[0072] It can be seen from Table 2 that in the technical solution provided by this application, when the sodium nitrate concentration is low, the ion exchange capacity becomes smaller, and NO 3- High temperature calcination can improve the limited pore structure of aluminosilicate; when the sodium nitrate concentration is high, too much nitrate enters the interior of the aluminosilicate, which easily causes the pores to collapse after calcination. Preferably, the concentration of the sodium nitrate solution is 1 mol / L to 6 mol / L.
[0073] The inorganic mesoporous materials of modified aluminosilicate prepared in Example 1, Examples 5-7 and Comparative Examples 3-4 were respectively used to carry out denitrification and phosphorus removal treatment steps for sewage of the same concentration. Before treatment, the initial concentration of ammonia nitrogen in the sewage was 20 mg / L, and the initial total phosphorus concentration was 1.0 mg / L. The dosage of the inorganic mesoporous materials of modified aluminosilicate was 40 g / L, and the reaction time was 2 days. The effects are shown in Table 3.
[0074] Table 3: Ammonia nitrogen and total phosphorus concentrations and removal rates before and after different solid-liquid ratios of aluminosilicate and sodium nitrate
[0075]
[0076] As can be seen from Table 3, in the technical solution provided by the present application, when the volume of the sodium nitrate solution is small, the cation exchange and nitrate attachment will be limited; when the volume of the sodium nitrate solution is too large, the effect on the modified aluminosilicate to improve the pollutant adsorption rate will not change much. Preferably, the volume of the nitrate solution corresponding to each 1g of the aluminosilicate particles is preferably 10mL to 60mL.
[0077] The inorganic mesoporous materials of modified aluminosilicate prepared in Example 1, Example 8 and Comparative Examples 5-6 were respectively used to carry out denitrification and phosphorus removal treatment steps for sewage of the same concentration. Before treatment, the initial concentration of ammonia nitrogen in the sewage was 20 mg / L, and the initial total phosphorus concentration was 1.0 mg / L. The dosage of the inorganic mesoporous materials of modified aluminosilicate was 35 g / L, and the reaction time was 2 days. The effects are shown in Table 4.
[0078] Table 4: Ammonia nitrogen, total phosphorus concentration and removal rate before and after different roasting temperatures
[0079]
[0080] As shown in Table 4, in the technical solution provided by the present application, if the calcination temperature is too low (lower than 400°C), the pore expansion effect cannot be significantly achieved; if the calcination temperature is too high (higher than 500°C), the aluminosilicate skeleton may collapse. Preferably, the calcination temperature is 400°C to 500°C.
[0081] Although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0082] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.
Claims
1. A method for preparing an inorganic mesoporous material of modified aluminosilicate, characterized in that: The steps include: S1. After crushing the aluminosilicate, screen out aluminosilicate particles of 80-100 meshes, wherein the specific surface area of the aluminosilicate is 14m² / g-16m² / g; S2, soaking the aluminosilicate particles obtained in step S1 in a nitrate solution with a concentration of 1 mol / L to 6 mol / L for 12 h to 24 h, wherein the volume of the nitrate solution corresponding to each 1 g of the aluminosilicate particles is 10 mL to 60 mL, filtering, drying at 95° C. to 110° C., and then calcining at 400° C. to 500° C. for 1 h to 2 h to obtain primary modified aluminosilicate particles, wherein the nitrate is any one of sodium nitrate and potassium nitrate; S3. Soak the primary modified aluminosilicate particles obtained in step S2 in a chitosan solution with a mass concentration of 3% to 5% and a temperature of 40°C to 60°C for 0.5h to 3h, wherein the chitosan solution is an alkaline chitosan solution with a pH value of 9.5 to 10.5, and then filter and wash with water, and dry at 95°C to 110°C to obtain an inorganic mesoporous material of modified aluminosilicate.
2. The method for preparing the inorganic mesoporous material of modified aluminosilicate according to claim 1, characterized in that: The aluminosilicate is at least one of sodium aluminosilicate, potassium aluminosilicate and calcium aluminosilicate.
3. The method for preparing the inorganic mesoporous material of modified aluminosilicate according to claim 2, characterized in that: In step S2, the concentration of the nitrate solution is 4 mol / L, the volume of the nitrate solution per 1 g of the aluminosilicate particles is 40 mL, and the soaking time is 12 h.
4. The method for preparing the inorganic mesoporous material of modified aluminosilicate according to claim 1 or 3, characterized in that: In step S2, the calcination temperature is 400° C. and the calcination time is 1 hour.
5. The method for preparing the inorganic mesoporous material of modified aluminosilicate according to claim 1, characterized in that: In step S3, the mass concentration of the chitosan solution is 5%, the temperature of the chitosan solution is 50° C., and the immersion time in the chitosan solution is 1 hour.
6. An inorganic mesoporous material of modified aluminosilicate prepared according to the preparation method according to any one of claims 1 to 5.
7. The inorganic mesoporous material of modified aluminosilicate according to claim 6, characterized in that: The specific surface area of the inorganic mesoporous material of modified aluminosilicate is 30m² / g to 40m² / g.
Citation Information
Patent Citations
Method for modifying natural zeolite by sodium nitrate combined roasting, product and application thereof
CN111054304A